Political Instability and Insecurity in Africa: Implications for African Union Agenda 2063 - Ukaeje, Obinna (Journal of Contemporary International Relations and Diplomacy, 2022)
The idea of the transformation of the Organization of African Unity (OAU) to the African Union (AU) in 1999, by African Heads of State and governments, was to accelerate the processes of regional economic integration in the continent. Thus, the AU came into being to enable the continent to play a significant role in global economic affairs, while addressing other multifaceted social, economic, and political problems that tend to hinder progress in the continent. However, after more than two decades of its transformation, and despite the adoption of Agenda 2063 which aims to accelerate economic progress in Africa, the continent remains at a crossroads in its struggle to grapple with the challenges of achieving its core objectives. Drawing data largely from secondary sources of information, the paper attempted a critical examination of the political instability and insecurity across many African states, especially as the continent strives towards achieving economic progress through the framework of Agenda 2063, and found out that political instability and insecurity are fundamental challenges standing against the actualization of the Agenda’s objectives. The paper, therefore, concluded that unless these challenges are mitigated, the Agenda 2063 will remain nothing but a document that cannot be actualized because the peace and security required to attend such an enviable feat is seriously in breach in a majority of the states of the Union. The paper recommended the entrenchment of democratic culture and constitutionalism as well as strengthening of existing institutions of governance as the first step towards achieving the desired peace and security that will ensure the economic progress of the continent.